When Project Commitment Leads to Learning from Failure: The Roles of Perceived Shame and Personal Control - Wang, Wenzhou; Wang, Bin; Yang, Ke; Yang, Chong; Yuan, Wenlong; Song, Shanghao (Frontiers in Psychology, 2018)
Although failure experience is regarded as the mother of success, scholars and entrepreneurs are prone to seek useful information from successful cases. In recent years, facing the extremely changing world, researchers gradually shift emphasis from successful experiences to failures. Previous studies mostly focused on the outcomes of learning from failure, while empirical researches toward antecedents and personal difference in the learning process are insufficient. In the current study, we build a model explore the relationship between project commitment and learning from failure, and test how emotion and cognition (attribution for failure) affect this process. The results show that project commitment is positively associated with learning from failure. Besides, shame and personal control attribution positively moderate the relationship between project commitment and learning from failure. Our study contributes to the empirical research of learning from failure, and the findings help managers apply them in practice.